The Utility of Speckle Tracking Echocardiographic Parameters in Predicting Atrial Fibrillation Recurrence After Catheter Ablation in Patients with Non-Valvular Atrial Fibrillation - Zeng D; Li L; Chang S; Zhang X; Zhong Y; Cai Y; Huang T; Wu J (Dove Medical Press, 2024)
Decai Zeng, Linyan Li, Shuai Chang, Xiaofeng Zhang, Yanfen Zhong, Yongzhi Cai, Tongtong Huang, Ji Wu Department of Ultrasonic Medicine, the First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, People's Republic of ChinaCorrespondence: Ji Wu, Department of Ultrasonic Medicine, the First Affiliated Hospital of Guangxi Medical University, 6 Shuangyong Road, Nanning, Guangxi Zhuang Autonomous Region, People's Republic of China, Email gxnnwuji@163.comBackground: Despite the efficacy of catheter ablation (CA) as a treatment for non-valvular atrial fibrillation (NVAF), many patients still experience atrial fibrillation (AF) recurrence after CA. This study aimed to evaluate the predictive value of speckle tracking echocardiographic (STE) parameters for AF recurrence post-ablation.Methods: A total of 380 NVAF patients treated with CA at the First Affiliated Hospital of Guangxi Medical University from January 2020 to March 2023 were prospectively recruited. The mean age was 59.4 ± 10.8 years, and 72.1% were male, including 150 patients (39.5%) with persistent AF and 230 patients (60.5%) with paroxysmal AF. STE was used to evaluate baseline left atrial (LA) function before CA within 48h. Over a median follow-up of 9 (interquartile range, 4- 17) months, AF recurrence occurred in 132 patients (34.7%).Results: The recurrence group showed lower left ventricular ejection fraction, LA reservoir strain (LASr), and conduit strain (LAScd), but higher LA stiffness than non- recurrence group (all P < 0.05). Multivariable Cox regression identified LA stiffness and LASr as independent risk factors. Time-dependent ROC analysis showed that LA stiffness (AUC 0.768, 95% CI 0.705- 0.831) and LASr (AUC 0.755, 95% CI 0.691- 0.820) were better at predicting 1-year AF recurrence than other risk factors. For 2-year AF recurrence post-catheter ablation, LA stiffness (AUC 0.866, 95% CI 0.804- 0.928) and LASr (AUC 0.860, 95% CI 0.800- 0.920) also demonstrated superior predictive performance. Kaplan-Meier curves showed a significant difference in AF recurrence rate for patients with LA stiffness > 0.55 and LASr ≤ 24.3% (Log rank P < 0.01).Conclusion: Evaluation of LA function using STE assists in stratifying the risk of AF recurrence in NVAF patients and guiding follow-up management. LASr and LA stiffness are independent predictors of AF recurrence following CA in NVAF patients, and potentially outperforming other morphological parameters.Keywords: non-valvular atrial fibrillation, catheter ablation, speckle tracking echocardiography, atrial fibrillation recurrence